The Causal Effect of Political Power on the Provision of Public Education: Evidence from a Weighted Voting System - Erik Lindgren; Per Pettersson-Lidbom; Björn Tyrefors (Research Institute of Industrial Economics (IFN), 2020)
In this paper, we estimate the causal effect of political power on the provision of public education. We use data from a historical nondemocratic society with a weighted voting system where eligible voters received votes in proportion to their taxable income and without any limit on the maximum of votes, i.e., the political system used in Swedish local governments during the period 1862-1909. We use a novel identification strategy where we combine two different identification strategies, i.e., a threshold regression analysis and a generalized event-study design, both of which exploit nonlinearities or discontinuities in the effect of political power between two opposing local elites: agricultural landowners and emerging industrialists. The results suggest that school spending is approximately 90-120% higher if the nonagrarian interest controls all of the votes compared to when landowners have more than a majority of votes. Moreover, we find no evidence that the concentration of landownership affected this relationship.
Keywords: O15; O43; H75; I25; N34; 330; Political Institutions; Education; Human Capital; Development